Sustainability reporting in cooperatives - Gamze Yakar Pritchard; Kıymet Çalıyurt (Risks, 2021)
The aim of the present study is to examine the sustainability reports of cooperatives, which may play an important role in achieving the sustainable development goals and help to identify which economic, environmental, and social sustainability indicators cooperatives are currently reporting. For this purpose, a total of 168 sustainability reports were examined for cooperatives that use the Global Reporting Initiative (GRI) G4 reporting, and that are included in the Sustainability Disclosure Database (SDD-GRI). As a result of this study, it was determined that the economic performance indicator disclosure levels of cooperatives that are active in the financial services sector are higher compared with those of cooperatives that are active in other sectors. In addition, it was also observed that the labor practices and decent work sub-category indicator disclosure levels of cooperatives active in the agriculture sector are lower compared to those of cooperatives that are active in the healthcare services and financial services sectors. Another outcome of this study was the finding that the social performance indicator disclosure levels for large-scale cooperatives are greater than those of small- and medium-sized (SME) cooperatives.
Keywords: 330; cooperative; sustainability reporting; global reporting initiative